HUBUNGAN KEMAMPUAN ORANGTUA MEMBACA AL-QUR'AN DAN MENDISIPLINKAN ANAK DENGAN KEMAMPUAN ANAK DALAM MEMBACA AL-QUR'AN DI DESA GUNUNG SARI RT03/03 KECAMATAN CITEUREUP KABUPATEN BOGOR - ., Sakilah (Universitas Islam Negeri Alauddin Makassar, 2021)
Al-Qur'an is the word of Allah SWT. The knowledge contained in the Qur'an is the knowledge of the truth of the Qur'an, be it in terms of knowledge, science, interpretation, nasikh and mansukh, al-muhkam, and al-mutasyabih. Guiding children in reading the Qur'an is an important thing to do because the goal is to enforce Islamic law. Allah SWT has guaranteed the blessings that parents get if their children always read the Qur'an. Parents should be good at reading the Koran before teaching their children. Thus it will make it easier to carry out the learning process of the Qur'an in children. Therefore, the importance of guiding and disciplining children in reading the Qur'an so that their ability to read the Koran is good. This study aims to determine how much the relationship between the ability of parents to read the Koran and discipline children with children's abilities. in reading the Koran in Gunung Sari village rt03 / 03, Citeureup sub-district, Bogor regency. This research uses quantitative research. This study took a total population of 17 children. data collection techniques in this study using (questionnaire). The results of this study are with a df of 15 with a value of r table at a significant level of 5%, it is known that r table 5% = 0.514 Thus the research hypothesis is that the Pearson Correlation (0.399) <r table (0.514) so that Ho is rejected Ha accepted by states that there is a positive relationship between the ability of parents to read the Qur'an and the ability of children to read the Qur'an. and it is stated that the Pearson Correlation (0.276) <r table (0.541) so that Ho is rejected and Ha is accepted by stating that there is a positive relationship between disciplining children and the child's ability to read the Qur'an.